Synthesis and Stabilization of Colloidal Perovskite Nanocrystals by Multidentate Polymer Micelles - Yuzheng Guo (ACS Applied Materials & Interfaces, 2017)
Lead halide perovskites have emerged as low-cost, high-performance optical and optoelectronic materials, however, their material stability has been a limiting factor for broad applications. Here, we demonstrate stable core–shell colloidal perovskite nanocrystals using a novel, facile and low-cost copolymer templated synthesis approach. The block copolymer serves as a confined nanoreactor during perovskite crystallization and passivates the perovskite surface by forming a multidentate capping shell, thus significantly improving its photostability in polar solvents. Meanwhile, the polymer nanoshell provides an additional layer for further surface modifications, paving the way to functional nanodevices that can be self-assembled or lithographically defined.